Anionic Phospholipids Induce Conformational Changes in Phosphoenolpyruvate Carboxylase to Increase Sensitivity to Cathepsin Proteases - Gandullo, Jacinto; Monreal, José-Antonio; Álvarez, Rosario; Díaz, Isabel; García-Mauriño, Sofía; Echevarría, Cristina (Frontiers in Plant Science, 2019)
Anionic phospholipids induce conformational changes in phosphoenolpyruvate carboxylase to increase sensitivity to cathepsin proteases. Jacinto Gandullo1, José-Antonio Monreal1, Rosario Álvarez 1; Isabel Díaz2, Sofía García-Mauriño1, Cristina Echevarría1*. 1Departamento de Biología Vegetal, Facultad de Biología, Universidad de Sevilla, Seville, Spain. 2 Centro de Biotecnología y Genómica de Plantas, Universidad Politécnica de Madrid, Campus de Montegancedo, Pozuelo de Alarcón, Madrid, Spain. * Correspondence: Cristina Echevarría echeva@us.es Word count: 8780 Number of figures: 6 Keywords: Phosphoenolpyruvate carboxylase, phospholipids, phosphatidic acid, proteolysis, conformational changes, cathepsin proteases, sorghum. Article type: Original Research 1. Abstract Phosphoenolpyruvate carboxylase (PEPC) is a cytosolic, homotetrameric enzyme that serves a variety of functions in plants, acting as the primary form of CO2 fixation in the C4 photosynthesis pathway (C4-PEPC). In a previous work we have shown that C4-PEPC bind anionic phospholipids, resulting in PEPC inactivation. Also, we showed that PEPC can associated with membranes and to be partially proteolyzed. However, the mechanism controlling this remains unknown. Using semi purified-PEPC from sorghum leaf and a panel of PEPC-specific antibodies, we analyzed the structural changes in PEPC induced by anionic phospholipids to cause the inactivation of the enzyme. Conformational changes observed involved the exposure of the C-terminus of PEPC from the native, active enzyme conformation. Investigation of the protease activity associated with PEPC demonstrated that cysteine proteases co-purify with the enzyme, with protease-specific substrates revealing cathepsin B and L as the major protease species present. The anionic phospholipid-induced C-terminal exposed conformation of PEPC appeared highly sensitive to the identified cathepsin protease activity and showed initial proteolysis of the enzyme beginning at the N-terminus. Taken together, these data provide the first evidence that anionic phospholipids promote not only the inactivation of the PEPC enzyme, but also its proteolysis.